2000
DOI: 10.1111/j.1365-2672.2000.tb05326.x
|View full text |Cite
|
Sign up to set email alerts
|

The public health significance of VTEC O157

Abstract: Surveillance of human VTEC O157 has been reported in several countries, based on laboratory evidence. The incidence is generally less than 10 per 100 000 (the highest incidence is in children), with regional variations and a marked seasonality. Laboratory selection criteria and reporting have contributed to, but cannot entirely explain, variations within and between countries. Surveillance data and outbreaks in definable cohorts indicate that the spectrum of illness ranges from diarrhoea through acute bloody d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…The strains from group B2 are usually responsible for extraintestinal infections (Picard et al, 1999;Johnson and Stell, 2000). The phylogenetic group D includes pathogenic strains such as E. coli O157:H7, which is highly virulent and can cause diarrhea, hemolytic uremic syndrome and hemorrhagic colitis (Parry and Palmer, 2000). Previous studies have demonstrated that group B2 E. coli strains are less resistant to antibiotics (Laroche et al, 2009;Moreno et al, 2006) and it is assumed that they tend to carry fewer integrons than the others phylogenetic E. coli groups (Skurnik et al 2005).…”
Section: Usa 4 % Of the Tetracycline Resistant Isolates Were Positivementioning
confidence: 99%
“…The strains from group B2 are usually responsible for extraintestinal infections (Picard et al, 1999;Johnson and Stell, 2000). The phylogenetic group D includes pathogenic strains such as E. coli O157:H7, which is highly virulent and can cause diarrhea, hemolytic uremic syndrome and hemorrhagic colitis (Parry and Palmer, 2000). Previous studies have demonstrated that group B2 E. coli strains are less resistant to antibiotics (Laroche et al, 2009;Moreno et al, 2006) and it is assumed that they tend to carry fewer integrons than the others phylogenetic E. coli groups (Skurnik et al 2005).…”
Section: Usa 4 % Of the Tetracycline Resistant Isolates Were Positivementioning
confidence: 99%
“…Approximately 11% of the illnesses recorded during a large E. coli O157:H7 outbreak in the United States in 1993 due to contaminated beef burgers were determined to be secondary infections (Bell et al 1994). In Wales, between 1990 and 1998, 17% of the identified cases of E. coli O157:H7 infection were the result of contact with an index case (Parry and Palmer 2000). The household transmission rate of E. coli O157:H7 infection in Wales between 1994 and 1996 was estimated to be 7%, with children aged 1-4 yr and adults aged 15-34 yr most likely to contract infection from an index case through household contacts.…”
Section: Person-to-person Transmissionmentioning
confidence: 99%
“…Although various pathogenic serotypes exist (43), E. coli O157:H7 has been the most frequently isolated in North America (50). Pathogenesis of E. coli O157:H7 is linked to numerous virulent factors (24), leading to pathological conditions such as hemorrhagic colitis, hemolytic uremic syndrome, thrombotic thrombocytopenic purpura, acute renal failure, and even death (6).…”
mentioning
confidence: 99%